Kinetic Characteristics of Ca2+-ATPase of Erythrocytes in PEO-1500 Presence - Zemlyanskikh, N. G.; Babijchuk, L. A.; Nikolchenko, A. Yu.; Tyagileva, V. P. (Problems of Cryobiology and Cryomedicine, 2003)
In the work it has been established, that the exocellular cryoprotectant PEO-1500 inhibits the activity of Ca2+-ATPase of erythrocytes. Kinetic analysis showed that the inhibition of enzyme activity was related to the Vmax alteration, but not to Km for catalytic center with a low affinity of Ca2+-ATPase. The highly affinic center of Ca2+-ATPase was not modified under PEO-1500 effect. The presence of cryoprotectant in the medium reduces the sensitivity of enzyme response of ATP hydrolysis to Ca2+ ions, as the result the erythrocyte Ca2+-ATPase functioning is activated in a lesser extent within the range of Ca2+ low concentrations and is inhibited in a greater extent for a high concentration range of this ion in comparison with the native erythrocytes. These data allow to suggest, that under PEO-1500 effect the Ca2+-ATPase ion-transporting function can be suppressed, and the efficiency of Ca-pump activity will decrease. The inhibition of Ca2+-ATPase activity is evidently caused by modifying the physical and chemical characteristics of plasma membrane under PEO-1500 effect.